Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

Encapsulated tannic acid protects against ETEC-induced intestinal damage via modulating gut microbiota and barrier function - Hang Gao; Ying Xiao; Tianjiao Wang; Ruohan Liu; Qiao Li (Food Research International, 2026)

Performance of micro-nanobubbles for synergistic control of ultrafiltration membrane fouling and emerging contaminants during nutrient recovery from biogas slurry - Wancen Liu; Ruohan Xia; Chuanren Qi; Yun Li; Guo Wei; Guoxue Li; Long D. Nghiem; Wenhai Luo (Chemical Engineering Journal, 2026)

Placental toxic metal concentrations and preterm birth: Modification by social stressors - Ruohan Liao; Adriana C. Vidal; James Harrington; John Thorp; David Skaar; Yukun Liu; Susan K. Murphy; David W. Sosnowski; Sara B. Johnson; Gang Peng; Jung-Ying Tzeng; Cathrine Hoyo (Reproductive Toxicology, 2026)

Mg/Fe-layered double hydroxide-loaded biochar enhances nitrogen retention and reduces geochemically reactive metal concentrations in paddy soil: Bacterial community responses - Hengxin Liu; Ruohan Li; Yueming Han; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

Emulsion gels stabilized by millet chaff prolamin–gallic acid or –sucralose conjugates: characterization, application in curcumin, and mechanism insights - Yan Li; Jie Liu; Hao Wang; Biao Ma; Zihao Zhang; Ling Dang; Yajun Zheng; Ruohan Liu; Yi Li (Food Chemistry, 2026)

Differential responses of plant C–N allocation and diazotrophic community structure to nitrogen fertilization in dwarf pea systems - Qiong Liu; Ruohan Yin; Linying Xu; Tin Mar Lynn; Jianping Chen; Zhenke Zhu; Tida Ge; Yalong Liu (European Journal of Soil Biology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Co-mitigating tire wear particles and their leachates across the life cycle: A critical review - Kejun Liao; Junyi Yu; Ruohan Huang; Wenjing Zhou; Yuwei Zhou; Junru Guo; Shengman Zhang; Chen Cai; Kaiming Peng; Xiangfeng Huang; Jia Liu (Water Research, 2026)

Application of POD-ANN reduced order model to fluid-thermal-structural coupling analysis in printed circuit heat exchangers - Hanxing Liu; Minyun Liu; Shenghui Liu; Yu Tang; Ruilong Liu; Junjie Fei; Yuanfeng Zan; Ruohan Zheng; Yanping Huang (Annals of Nuclear Energy, 2026)

Combined organic pollutants and heavy metals distinctly alter microbial assembly and metabolism of Cynodon dactylon (L.) Pers. within industrial green belts - Junyi Yu; Shuangqiang Li; Junru Guo; Ruohan Huang; Chen Cai; Kaiming Peng; Lijun Lu; Xiangfeng Huang; Jia Liu (Journal of Environmental Sciences, 2026)

Heat transfer and dynamic behavior of wall-adhered carbon dioxide droplets: power-law correlation and the cryogenic ring effect - Qifan Wang; Minyun Liu; Yanping Huang; Shanfang Huang; Ruohan Zheng; Houjun Gong (Annals of Nuclear Energy, 2026)

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

High temperature favors sedimentary organic carbon fixation potential via chemoautotrophy and iron fraction transformation in urban artificial lakes - Ruohan Huang; Junru Guo; Kaiming Peng; Chen Cai; Xiangfeng Huang; Qiaofeng Wu; Jia Liu (Water Research, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Host genotype-enriched rhizosphere microbes enhance pea (Pisum sativum L.) yield - Qinwen Yang; Qiong Liu; Ke Dong; Kaile Zhang; Chuanfa Wu; Ruohan Yin; Linying Xu; Zhijuan Feng; Tao Yang; Tida Ge (Plant and Soil, 2026)

Analysis of the blowdown of supercritical carbon dioxide from simple vessel - Fengyuan Tian; Minyun Liu; Yanping Huang; Ruohan Zheng; Yangle Wang; Houjun Gong; Yu Tang; Tianzeng Liu; Jinghan Hu; Haohan Yuan; Yuan Zhou (Annals of Nuclear Energy, 2026)

Metal-free C H functionalization unlocks multifunctional luminescent PEGs for biomedical imaging and therapy - Weiping Liu; Qinyue Guo; Lifang Ma; Ruohan Li; Jiajia Ren; Haixia Jiang; Gang Wang; Rong Zeng (Chemical Engineering Journal, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Genome-resolved metagenomic insights into cornstalks-mediated reduction of pathogens and antibiotic resistomes during passively aerated static composting of swine manure - Ruohan Xia; Tong Shi; Wancen Liu; Guoxue Li; Suli Zhi; Wenhai Luo; Zhicheng Xu (Journal of Environmental Management, 2026)

Co-exposure to multiple fine particulate matter constituents and adults obstructive sleep apnoea (OSA) in Southern China - Suhan Wang; Gongbo Chen; Peipei Dong; Hailin Xiong; Yuewei Liu; Ruohan Zhou; Ranxu Zhang; Qiong Ou (Environmental Pollution, 2026)

Inheritance of depleted mantle 186Os signatures in Tibetan ophiolitic chromitites - Yong Xu; Qing Xiong; Bin Qin; Ruohan Gao; Xiaohan Gong; Degao Zhai; D. Graham Pearson; Jingao Liu (Earth and Planetary Science Letters, 2026)

Levels and associated potential ecological risks of heavy metals in surface sediments from wetlands in the western Yellow River Delta - Ruohan Zhang; Zaiwang Zhang; Junxia Yang; Xu Zhang; Shanshan Liu; Jianchao Jin; Guangwu Liu; Changqing Shan; Jian Li; Jianhui Tang (Regional Studies in Marine Science, 2026)

A novel TpAQ-COF/ZnS/ZnIn2S4 ternary photocatalyst with double Z-scheme heterostructure for visible light photocatalytic degradation of 2,4-dichlorophenol - Ruohan Sun; Yuqing Xia; Tingting Ma; Hui Yu; Guixia Liu; Jinxian Wang; Wensheng Yu; Feng Sun; Xiangting Dong (Journal of Cleaner Production, 2026)

A sensitive method for rapid determination of 256 semi-volatile organic compounds (SVOCs) in water by solid-phase extraction and GC–MS/MS - Youchang Zhu; Ruohan Sun; Yanran Dong; Yan Liu; Yupeng Chen; Zhiquan Yuan; Baozhu Pan; Nan Xu (Journal of Environmental Sciences, 2026)

Gallic acid-reinforced Rana chensinensis ovum protein isolates-Gellan gum thermally reversible emulsion gel: Insight of the structure and potential applications in dysphagia management - Ruixue Liu; Min Gao; Li Zhang; Shihan Wang; Ying Yang; Jing Bai; Ruohan Wang; Yongsheng Wang; Zhihan Wang (Food Research International, 2025)

Surface nitridation of Si enabled gradient artificial solid electrolyte interface and self-optimized structural evolution - Zhenyi Huang; Ruohan Yu; Jinshuai Liu; Yuxia Zhong; Lei Zhang; Liang Zhou (Science Bulletin, 2025)

Freeze–thaw impacts on the mechanical behavior of silty clay: Insights from experimental and DEM investigation - Run Liu; Rui Zhang; Ruohan Sun (Bulletin of Engineering Geology and the Environment, 2025)

One-step molding to prepare durable dual superlyophobic composites for non-loss mass transfer, immiscible solvent separation, and CO2 bubble removal - Chang-Lian Xu; Xingyue Wu; Yuqing Song; Jialin Liu; Ruohan Xiong; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Xin Qi; Guochun Lv; et al. (Journal of Environmental Chemical Engineering, 2025)

Dynamics of wall bubbles in flash evaporation systems: Heterogeneous expansion and microlayer development - Qifan Wang; Junren Hou; Shanfang Huang; Fangbei Chen; Minyun Liu; Ruohan Zheng; Yanping Huang; Lie Quan; Houjun Gong; Yu Tang (Annals of Nuclear Energy, 2025)

Long-term exposure to dust in fine particulate matter and post-stroke functional impairment—Findings from the China National Stroke Screening Surveys - Zhaoyang Pan; Xueyan Han; Man Cao; Ruohan Wang; Jian Guo; Wei Sun; Jiarun Mi; Yuanli Liu; Tao Xue; Tianjia Guan (Journal of Hazardous Materials, 2025)

Carboxylesterase 1 regulates peroxisome proliferator-activated receptor gamma to inhibit the growth and metastasis of breast cancer cells - Jingli Wen; Lei Geng; Ruohan Wang; Xiaolei Zhang; Yanmin Sui; Xiaofang Liu; Xin Han (Journal of Molecular Histology, 2025)

Accurate identification and formation mechanism unraveling of radicals in UV-induced peracetic acid activation system using in-situ electron paramagnetic resonance - Long Chen; Ruohan Zhang; Zhaoli Liu; Fan Li; Boyu Huang; Wen Liu (Science Bulletin, 2025)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

Graft copolymerization synthesis of chitosan-polyferric sulfate composite coagulant to improve biogas slurry treatment toward effective irrigation - Ruohan Xia; Wancen Liu; Long D. Nghiem; Dingge Cao; Guoxue Li; Wenhai Luo (Journal of Environmental Management, 2025)

Corrigendum to “Distribution characteristics, risk assessment, and quantitative source apportionment of typical contaminants (HMs, N, P, and TOC) in river sediment under rapid urbanization: A study case of Shenzhen river, Pearl River Delta, China” [Process Saf. Environ. Prot. 162 (2022) 155–168] - Ying Zhang; Wei Mao; Ruohan Li; Yang Liu; Peng Wang; Zelin Zheng; Yuntao Guan (Process Safety and Environmental Protection, 2025)

Development of system analysis code and its application in transient simulation of supercritical CO2 Brayton cycle direct cooled reactors - Haijie Wu; Minyun Liu; Shenghui Liu; Jiatao Meng; Shuangqing Chen; Ruohan Zheng; Yanping Huang; Houjun Gong; Xiaoliang Zhu; TianYang Xing; Mudi Jiang (Annals of Nuclear Energy, 2025)

The combined effects of microplastics and their additives on mangrove system: From the sinks to the sources of carbon - Junru Guo; Mingqing Yang; Ruohan Huang; Junyi Yu; Kaiming Peng; Chen Cai; Xiangfeng Huang; Qiaofeng Wu; Jia Liu (Science of The Total Environment, 2025)

A novel approach to estimate land surface temperature from landsat top-of-atmosphere reflective and emissive data using transfer-learning neural network - Shuo Xu; Dongdong Wang; Shunlin Liang; Aolin Jia; Ruohan Li; Zhihao Wang; Yuling Liu (Science of The Total Environment, 2024)

Computational modeling of near-fault earthquake-induced landslides considering stochastic ground motions and spatially varying soil - Ruohan Wang; Guan Chen; Yong Liu; Michael Beer (Engineering Structures, 2024)

Photoexcitation-induced efficient detoxification and removal of arsenite in contaminated water by a layered double hydroxide-supported polyacrylate stabilized ferrous sulfide composite - Wei Mao; Yibing Li; Lixun Zhang; Xuewu Shen; Yang Liu; Ruohan Li; Yuntao Guan (Journal of Hazardous Materials, 2024)

A novel chitosan and polyferric sulfate composite coagulant for biogas slurry pretreatment by simultaneous flocculation and floatation: Performance and underlying mechanisms - Ruohan Xia; Wancen Liu; Long D. Nghiem; Dingge Cao; Yun Li; Guoxue Li; Wenhai Luo (Water Research, 2024)

Peridynamics-based large-deformation simulations for near-fault landslides considering soil uncertainty - Ruohan Wang; Shaofan Li; Yong Liu; Xuan Hu; Xin Lai; Michael Beer (Computers and Geotechnics, 2024)

A DEM-based approach for modeling the thermal-mechanical behavior of frozen soil - Ruohan Sun; Run Liu; Huan Zhang; Rui Zhang; Yu Jiang; Ruilong Yin (European Journal of Environmental and Civil Engineering, 2024)

Unveil the potential in hydrogen activation and spillover towards NiMoS by Ni3S2 - A theoretical study - Xiaodong Liu; Hangyu He; Lijun Hu; Xiaohui Zhang; Ruohan Wang; Xuemin Yan (Fuel, 2024)

Long-term exposure to the components of fine particulate matters and disability after stroke: Findings from the China National Stroke Screening Surveys - Hong Lu; Ruohan Wang; Jiajianghui Li; Mingkun Tong; Man Cao; Hengyi Liu; Qingyang Xiao; Yixuan Zheng; Yuanli Liu; Tianjia Guan; Tao Xue (Journal of Hazardous Materials, 2023)

Solution-catalyzed carbothermal reduction of argo-waste SiO2 enables low-temperature and fast synthesis of Si(Ⅱ)-C anode - Zi'ang Liu; Ruohan Yu; Shaohua Zhu; Jiashen Meng; Xuanpeng Wang; Chaojiang Niu; Lianmeng Cui; Fan Qiao; Junjun Wang; Liqiang Mai (Chemical Engineering Journal, 2023)

DEM investigation of the mechanical behavior of frozen soil along various stress paths - Ruohan Sun; Run Liu; Huan Zhang; Chun Liu; Chengfeng Li (Bulletin of Engineering Geology and the Environment, 2023)

Activation persulfate for efficient tetrabromobisphenol A degradation via carbon-based materials: Synergistic mechanism of doped N and Fe - Zhengfang Zhang; Yang Liu; Ying Zhang; Ruohan Li; Yuntao Guan (Journal of Hazardous Materials, 2023)

Occurrence and fate of antibiotics in swine waste treatment: An industrial case - Wancen Liu; Yongfang Wang; Ruohan Xia; Xiangrui Ding; Zhicheng Xu; Guoxue Li; Long D. Nghiem; Wenhai Luo (Environmental Pollution, 2023)

Polybrominated diphenyl ethers in water, suspended particulate matter, and sediment of reservoirs and their tributaries in Shenzhen, a mega city in South China - Tingting Zhu; Youchang Zhu; Yunlang Liu; Chen Deng; Xiujuan Qi; Jinling Wang; Zhizhi Shen; Donggao Yin; Yihong Liu; Ruohan Sun; Weiling Sun; Nan Xu (Environmental Science and Pollution Research, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Morphology and mass spectrometry-based chemical profiling of peltate glandular trichomes on Mentha haplocalyx Briq leaves - Ruohan Liu; Yutuan Wang; Conglian Liang; Zhijuan Zheng; Xiuwei Du; Zhanhu Cui; Yongqing Zhang; Hongyan Liu (Food Research International, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Sulfur-containing benzofurans and α-pyrones from the mangrove-derived fungus Talaromyces sp. WHUF0341 - Ruohan Zhang; Jinxin Zhang; Ruiyun Huo; Yaxin Xue; Kui Hong; Ling Liu (Frontiers in Marine Science, 2022)
Two new sulfur-containing benzofurans, talarobenzofurans A and B ( 1 and 2 ), one new benzofuran talarobenzofuran C ( 3 ) and two new α -pyrones talaropyrones A and B ( 5 and 6 ), along with five known compounds eurothiocin A ( 4 ), nodulisporipyrone A ( 7 ), peniazaphilin B ( 8 ), ramulosin ( 9 ) and 6-hydroxyramulosin ( 10 ) were isolated and identified from the culture extract of the mangrove-derived fungus Talaromyces sp. WHUF0341 guided by OSMAC (one strain-many compounds) strategy. Their structures were established by extensive spectroscopic data analysis, the modified Mosher’s method and electronic circular dichroism (ECD) calculations. Structurally, compounds 1 and 2 possesed the unique thioester moiety derived from benzofuran and 2-hydroxy-3-mercaptopropionic acid, which was rarely-observed in natural products. The α -glucosidase inhibitory and antibacterial activities of the isolated compounds were evaluated. Compounds 3 and 4 exhibited inhibitory effects against α -glucosidase activity with IC 50 values of 48.9 ± 2.16 and 8.8 ± 1.08 µM, respectively. The inhibitory type of 3 on α -glucosidase was determined as non-competitive-type inhibition with K i value of 242.3 μM by using Lineweaver-Burk double reciprocal and Dixon single reciprocal plots. Meanwhile, the binding model of 3 and 4 with α -glucosidase was determined by molecular docking assay. The biosynthetic pathways of compounds 1 − 4 were also proposed. This study suggested that benzofurans 3 and 4 could be potential lead compounds for the hypoglycemic drugs.

Correction to: Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2022)

Characteristics and Cause Analysis of Variations in Light Precipitation Events in the Central and Eastern Tibetan Plateau, China, During 1961–2019 - Kaifang Li; Liguo Cao; Zhengchao Zhou; Lei Jiao; Ning Wang; Ruohan Liu (Chinese Geographical Science, 2022)

Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2021)

Structural architecture of Neoproterozoic rifting depression groups in the Tarim Basin and their formation dynamics - Bizhu He; Cunli Jiao; Taizhu Huang; Xingui Zhou; Zhihui Cai; Zicheng Cao; Zhongzheng Jiang; Junwen Cui; Zhuoyin Yu; Weiwei Chen; Ruohan Liu; Xiaorui Yun; et al. (Science China Earth Sciences, 2019)

Constant hypoxia inhibits osteoclast differentiation and bone resorption by regulating phosphorylation of JNK and IκBα - Zhenzhen Ma; Ruohan Yu; Jinxia Zhao; Lin Sun; Leilei Jian; Changhong Li; Xiangyuan Liu (Inflammation Research, 2019)

The Protective Effect of Selenium on the Chicken Pancreas against Cadmium Toxicity via Alleviating Oxidative Stress and Autophagy - Ruohan Liu; Tiantian Jia; Yuan Cui; Hongjin Lin; Shu Li (Biological Trace Element Research, 2018)

Controlling factors and accumulation model of hydrocarbon reservoirs in the Upper Cretaceous Yogou Formation, Koulele Area, Termit Basin, Niger - Xuying Wang; Lunkun Wan; Zaixing Jiang; Ruohan Liu; Xiabin Wang; Wangxin Tang; Yi Gao; Shengqian Liu; Wenmao Xu (Journal of Earth Science, 2017)

Reservoir characteristics and controlling factors of Silurian Lower Kepingtage Formation in Tahe area, Tarim Basin, NW China - Ruohan Liu; Zaixing Jiang; Ming Wang; Weili Yang; Jingxiang Guo; Minghao Wu; Yi Gao; Shanyazi Wei; Zhihong Nie; Hong He (Journal of Earth Science, 2017)

Sedimentary characteristics and formation mechanisms of lacustrine beach-bars in the fourth member of the Shahejie Formation in the Shubei area, western depression of the Liaohe Oilfield, China - Yi Gao; Xiaolong Jiang; Fang Liu; Xuying Wang; Ruohan Liu (Journal of Earth Science, 2017)

Evaluation of site-specific tactics using bifenazate and Neoseiulus californicus for management of Tetranychus urticae (Acari: Tetranychidae) in strawberries - Ruohan Liu; Teresia W. Nyoike; Oscar E. Liburd (Experimental and Applied Acarology, 2016)

miRNAs play essential roles in the floral thermogenesis of Magnolia denudata (Magnoliaceae) - Xiangyu Liu; Dechang Cao; Xiangyu Ji; Zhixiang Zhang; Yanwei Wang; Ruohan Wang (Trees, 2015)

Temperature regulation of floral buds and floral thermogenicity in Magnolia denudata (Magnoliaceae) - Ruohan Wang; Xiangyu Liu; Shulin Mou; Sai Xu; Zhixiang Zhang (Trees, 2013)